2021
DOI: 10.1051/parasite/2021061
|View full text |Cite
|
Sign up to set email alerts
|

Treatment against helminths in Norwegian sheep: a questionnaire-based survey

Abstract: A questionnaire was distributed to 5487 farmers throughout Norway in order to obtain information about management practices regarding helminth infections in sheep. In addition, the farmers’ perceptions of helminths and anthelmintic efficacy were investigated. Most farmers (80%) treated prophylactically against nematodes, and 24% also used prophylactic treatment against Fasciola hepatica. Overall, few farmers (11%) used parasitological analysis as a tool to assess the timing of treatment, but rather based it on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…However, parasitological analysis was not used prior to treatment and was evaluated later in the treatment schedule, which seems to be a common feature among herders in Ordos. This is similar to the results of the 1.5 insect repeats performed annually in Norwegian herders every year; however, Norwegian herders performed more prophylactic insect repeats, and 53% did not experience gastrointestinal nematode problems [ 33 ]. The survey also found that 46.38% (508/1163) of herders would increase the anthelmintics dose based on recommendations or without authorization, fundamentally contributing to the development of anthelmintic resistance( Figure 9 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, parasitological analysis was not used prior to treatment and was evaluated later in the treatment schedule, which seems to be a common feature among herders in Ordos. This is similar to the results of the 1.5 insect repeats performed annually in Norwegian herders every year; however, Norwegian herders performed more prophylactic insect repeats, and 53% did not experience gastrointestinal nematode problems [ 33 ]. The survey also found that 46.38% (508/1163) of herders would increase the anthelmintics dose based on recommendations or without authorization, fundamentally contributing to the development of anthelmintic resistance( Figure 9 ).…”
Section: Discussionsupporting
confidence: 84%
“…Flocks were recruited from the Norwegian sheep recording system, with data previously collected by a questionnaire as described earlier [22]. Briefly, the dataset comprised 1378 sheep farmers, and all counties of Norway were represented.…”
Section: Selection Of Flocksmentioning
confidence: 99%
“…The use of chemical drugs to control parasitism has become increasingly inefficient, due to anthelmintic resistance developed by most parasite species in herbivores throughout the world [7][8][9][10]. For example, a survey of parasite control practices in Norway found that 80% of sheep producers used anthelmintics without knowing the parasitological status of the herd [11]. Only 11% performed diagnostic tests to support their decision-making for the use of anthelmintics.…”
Section: Introductionmentioning
confidence: 99%